Menyelami Hyperreality dalam Globalisasi Budaya: Hegemoni Korean Wave terhadap Konstruksi Sosial Indonesia (2021-2022) - Fernando, Jason (Journal of Comprehensive Science, 2025)
The Korean Wave has constructed a significant cultural force, shaping global identities through entertainment media such as K-pop, K-dramas, and K-movies. Contextually, this study explores how the Korean Wave creates a hyperreality that dominates the consciousness of global society, including Indonesia. Using Jean Baudrillard's theoretical framework of hyperreality, the research demonstrates how South Korean culture, as represented through media, transcends mere reflection of reality to create a new reality that supplants local identities. Through qualitative analysis, the findings reveal that the Korean Wave has become a powerful soft power tool for South Korea, redefining cultural preferences and displacing local traditions. In Indonesia, this phenomenon is evident in the widespread popularity of K-pop and K-dramas, which dominate media consumption and influence lifestyles, behaviors, and mindsets. Under the lens of hyperreality, South Korean culture is not only adopted but also idolized as an idealized reality. The study highlights the implications of the Korean Wave in fostering cultural hegemony, which weakens the uniqueness of local identities. It underscores the need for critical awareness of hyperreality’s influence and emphasizes efforts to preserve local culture amid the intensifying wave of cultural globalization driven by the Korean Wave.